The effect of empowerment education on depression level and laboratory indicators of patients treated with hemodialysis: a meta-analysis - Ji Yu-Nan; Liu Yan-Hui; Xie Ling-Li; Li Chen-Yang; Hou Zhen-Hua (Sciendo, 2019)
The objective of this study was to evaluate the effect of empowerment education on depression level and laboratory indicators of patients treated with hemodialysis.